Where the buffaloes begin - Baker, Olaf.; Gammell, Stephen (New York Puffin Books, 1985)
After hearing the legend retold by the tribe's oldest member, Little Wolf hopes to someday witness the beginning of the buffaloes at the sacred lake.
Originally published: New York : F. Warne, 1981.
Keywords: Children's stories, American; Indians of North America -- Fiction; Bison -- Fiction